Enantioselective Construction of Quaternary Carbon Stereocenter via Palladium-Catalyzed Asymmetric Allylic Alkylation of Lactones - Li, Xiao-Hui; Wan, Shi-Li; Chen, Di; Liu, Qing Rong; Ding, Chang-Hua; Fang, Ping; Hou, Xue-Long (Synthesis, 2016)
An efficient and practical method for the synthesis of α,α-disubstituted six-membered lactones was developed. Enantioselective construction of quaternary carbon centers by utilizing Pd-catalyzed asymmetric allylic alkylation proved its feasibility.
Keywords: palladium; allylic alkylation; asymmetric catalysis; lactones; quaternary carbon